Creative Economy Innovation Through “Batik Tulis” with Natural Dyes as a Sustainable Development Solution - Pitri, Alisyah; Kuswanto, Kuswanto; Pitriani, Pitriani; Aji , Sugeng Purnama; Sarmila, Sarmila; Hardiana, Deasy; Aca, Ambo (CV. Zabags Qu Publish, 2023)
This research begins with the conditions of UKM Batik Fitris', which is a forum for people to be able to work, be creative and be productive as entrepreneurs, namely by producing batik. The selection of hand-written batik products is based on the capabilities of the village community and also considers low-risk products. The results achieved from this community service activity are changing people's mindsets into effective entrepreneurs with a batik learning program made from superior natural dyes. In this community service activity, the method used is a qualitative and intensive approach, namely about the community receiving intensive entrepreneurial learning and mentoring from teachers and practitioners working in the batik field. The use of natural materials as batik dyes is intended to avoid causing waste that is harmful to living creatures or the surrounding environment